2020
DOI: 10.1002/pbc.28397
|View full text |Cite
|
Sign up to set email alerts
|

COVID‐19 infection in children and adolescents with cancer in Madrid

Abstract: far, with mild-moderate disease, and only two of them required oxygen therapy, in line with general pediatric population data. 3 In conclusion, the prevalence of COVID-19 infection among children with cancer in Madrid is 1.3%. Although this patient population is managed as high risk, the clinical features are milder and the prognosis better than in the adult population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
153
8
12

Year Published

2020
2020
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 125 publications
(187 citation statements)
references
References 7 publications
7
153
8
12
Order By: Relevance
“…Most of the reported patients (68%) were from the states of Madrid and Catalonia, the two most affected areas in Spain 13 . Fifteen of the patients included in the present study were previously reported recently by de Rojas et al 14 . Initial experiences from Italy (Lombardy), 15 China (Wuhan), 16,17 and Europe suggest a low number and severity of COVID‐19 cases in this patient population, 6 contrary to France, where a higher incidence of critical patients was observed 18 .…”
Section: Characteristics Nmentioning
confidence: 61%
“…Most of the reported patients (68%) were from the states of Madrid and Catalonia, the two most affected areas in Spain 13 . Fifteen of the patients included in the present study were previously reported recently by de Rojas et al 14 . Initial experiences from Italy (Lombardy), 15 China (Wuhan), 16,17 and Europe suggest a low number and severity of COVID‐19 cases in this patient population, 6 contrary to France, where a higher incidence of critical patients was observed 18 .…”
Section: Characteristics Nmentioning
confidence: 61%
“…So, the incidence of COVID-19 in children with cancer in Madrid has recently been reported and is 1.3% higher than in the general pediatric population. 2 Table 1. We identified eight children with a median age of 10 years old (range 1-12), which is an incidence of 3% of the pediatric HSCT performed annually in Spain.…”
Section: Covid-19 In Pediatric Hematopoietic Stem Cell Transplantatiomentioning
confidence: 99%
“…Despite the concerns that chemotherapy-related immunosuppression is a risk factor to develop severe disease with Covid19, there is growing evidence that coronavirus-related mortality is extremely rare in pediatric cancer patients. 5,9,10 in pediatric cancer patients warrants that we reconsider our approach to the design of pediatric cancer services in the event of a second peak of Covid19 and future such pandemics. 12…”
Section: Impact Of Covid19 On a Tertiary Care Pediatric Oncology And mentioning
confidence: 99%